2011
DOI: 10.1186/1471-2148-11-217
|View full text |Cite
|
Sign up to set email alerts
|

Speciation in little: the role of range and body size in the diversification of Malagasy mantellid frogs

Abstract: BackgroundThe rate and mode of lineage diversification might be shaped by clade-specific traits. In Madagascar, many groups of organisms are characterized by tiny distribution ranges and small body sizes, and this high degree of microendemism and miniaturization parallels a high species diversity in some of these groups. We here investigate the geographic patterns characterizing the radiation of the frog family Mantellidae that is virtually endemic to Madagascar. We integrate a newly reconstructed near-complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(164 citation statements)
references
References 74 publications
7
155
2
Order By: Relevance
“…As a MCP spans the whole area between the sampled localities of a species, our topographic complexity measure is a simplified estimate that characterizes the entire region where dispersal events might have occurred in the past, regardless of range discontinuities and the current distribution of suitable habitats. However, considering the limited number of locality records available for most species, the calculations using MCPs may be more realistic than fine-scale mapping or ecological niche modeling (Wollenberg et al 2011) and from a biogeographic perspective still constitute an adequate estimate of habitat heterogeneity and potential barriers to gene flow.…”
Section: Explanatory and Response Variablesmentioning
confidence: 99%
“…As a MCP spans the whole area between the sampled localities of a species, our topographic complexity measure is a simplified estimate that characterizes the entire region where dispersal events might have occurred in the past, regardless of range discontinuities and the current distribution of suitable habitats. However, considering the limited number of locality records available for most species, the calculations using MCPs may be more realistic than fine-scale mapping or ecological niche modeling (Wollenberg et al 2011) and from a biogeographic perspective still constitute an adequate estimate of habitat heterogeneity and potential barriers to gene flow.…”
Section: Explanatory and Response Variablesmentioning
confidence: 99%
“…We determined changes in area occupancy, rate of area change, the direction of range shifts (across both longitudes and latitudes) and fragmentation index (DIÂŽ) between climate periods. 57,58 We ran our results in two ways: first with a full suite of 37 species and second with 34 species (excluding those species with less than 10 species records, to avoid model over-fitting 59 ). We found that the results in both attempts were almost identical and that patterns remained largely similar and thus report results of the analysis considering a full suite of 37 species.…”
Section: Volume 111 | Number 11/12mentioning
confidence: 99%
“…The extraordinary proportion of family-level endemism in Madagascar, and the long isolation from non-Malagasy sister lineages, provide a unique opportunity to study the mechanisms driving divergence and diversification in situ 22 . Over the past decade, numerous mechanisms and models have been formulated to explain biodiversity distribution patterns and species diversification in Madagascar, pertaining to environmental stability (or instability), solar energy input, geographic vicariance triggered by topographic or habitat complexity, intrinsic traits of organisms or stochastic effects [23][24][25][26][27][28][29][30][31] . Evidence has supported numerous hypotheses, though this evidence has typically been marshalled from limited taxa or groups of taxa with restricted phylogenetic diversity.…”
mentioning
confidence: 99%